Spatial Organization of Osteoclastic Coupling Factors and Their Receptors at Human Bone Remodeling Sites - Borggaard, Xenia G.; Nielsen, Malene H.; Delaisse, Jean-Marie; Andreasen, Christina M.; Andersen, Thomas L. (Frontiers in Molecular Biosciences, 2022)
The strictly regulated bone remodeling process ensures that osteoblastic bone formation is coupled to osteoclastic bone resorption. This coupling is regulated by a panel of coupling factors, including clastokines promoting the recruitment, expansion, and differentiation of osteoprogenitor cells within the eroded cavity. The osteoprogenitor cells on eroded surfaces are called reversal cells. They are intermixed with osteoclasts and become bone-forming osteoblast when reaching a critical density and maturity. Several coupling factors have been proposed in the literature, but their effects and expression pattern vary between studies depending on species and experimental setup. In this study, we investigated the mRNA levels of proposed secreted and membrane-bound coupling factors and their receptors in cortical bone remodeling events within the femur of healthy adolescent human controls using high-sensitivity RNA in situ hybridization. Of the proposed coupling factors, human osteoclasts showed mRNA-presence of LIF, PDGFB, SEMA4D, but no presence of EFNB2, and OSM. On the other hand, the osteoblastic reversal cells proximate to osteoclasts presented with LIFR, PDGFRA and PLXNB1, but not PDGFRB, which are all known receptors of the proposed coupling factors. Although EFNB2 was not present in mature osteoclasts, the mRNA of the ligand-receptor pair EFNB2:EPHB4 were abundant near the central blood vessels within intracortical pores with active remodeling. EPHB4 and SEMA4D were also abundant in mature bone-forming osteoblasts. This study highlights that especially LIF:LIFR, PDGFB:PDGFRA, SEMA4D:PLXNB1 may play a critical role in the osteoclast-osteoblast coupling in human remodeling events, as they are expressed within the critical cells.